Juozas Šibaila-Merainis - Kripienė, Enrika (Genocidas ir rezistencija, 2021)
During the investigation it was established that the case of Juozas Šibaila, one of the freedom fighters, can be regarded as an individual’s voluntary act of joining the guerrilla struggles. His decision most likely was determined by the factors between some groups. First of all, these were national and cultural values and the position on the issue of defence of the state. They are testified to by professional (teacher’s) activities and his active participation in different public organisations: the Lithuanian Riflemen’s Union, the Lithuanian National Youth Union ‘Jaunoji Lietuva’ (Young Lithuania), also, possible cooperation with intelligence of Lithuania, organising local rebel groups in 1941, membership in the Local Force. This has to be assumed that it was purely personal reasons that greatly influenced the crucial decision to become a partisan – the desire to take revenge on the Soviets for deporting his family, the perception that there was nowhere to draw back – Juozas Šibaila, as an unreliable social element, had been the focus of the repressive structures of the occupiers since 1940. After the re-occupation, he was threatened with being taken to court and sentenced to death for taking part in the persecutions of Soviet activists and for other kinds of activities carried out in the summer of 1941. Juozas Šibaila, a teacher and an active propagator of nationality, had the authority and enjoyed high reputation in the environs of his place of residence, which he always tried to maintain and justify; hence, his early joining armed resistance, organising the first groups of partisans seems quite natural. His work in the headquarters of different underground structures where he was responsible for publishing the press and proclamations, preparing documents necessary for centralisation or their drafts, successful attempts to draw as many teachers in the fights for freedom as possible, which took the greatest part of time of Juozas Šibaila as a partisan, as well as the analysis of his personal correspondence, allows us to state that this person was perfectly aware of the importance and significance of public, ideological-intellectual component to the fights for freedom. Such external attributes as codenames of Diedukas and Merainis which are atypical of a freedom fighter, the appearance resembling an ordinary peasant, suggest that the image of a fighter-hero was alien to him. He was a strict, authoritative and respected leader of partisans who managed to establish close, family relations with his brothers-in-arms. The importance and significance of Juozas Šibaila to the post-war armed underground is undeniable. In his ideological texts Juozas Šibaila-Merainis spoke mainly about political aspirations of the Union of Lithuanian Freedom Fighters (ULFF) and moral-spiritual side of the fights. According to him, close links of democracy and Christian morality relatedd these spheres. He tended to treat partisan resistance to the Soviets, first and foremost, as a struggle for the well-being of all humanity determined and inspired by the Lord. Having examined Juozas Šibaila’s written legacy in this field, as well as the way he was valued by the members of the underground, it can be stated that, on the one hand, the majority of the values and concepts fostered therein may be fundamental and inseparable from armed post-war resistance, and, on the other hand, their presentation and the chosen means of expression seemed to the majority of the partisans difficult to understand and were unacceptable. It might be that a large part of partisans, unlike Juozas Šibaila, imagined fights for freedom simply as war waged by the members of the underground for freedom of the state rather than that of an individual. Consequently, though Merainis’ above-mentioned texts were significant and valuable, in some cases it cannot be stated that they had a considerable impact on the world outlook of an ordinary partisan or a common peasant.